Modified hysteresis current controller of half bridge bidirectional DC-DC converter using chassis dynamometer for electric vehicle - Nurul Azwa, Othman (2017)
The advancement of research and development for Electric Vehicle (EV) has pushed a similar advancement in the EV performance test and measurement. Traditionally, chassis dynamometer is used to measuring power delivered from Vehicle Under Test (VUT) typically by Internal Combustion Engine (ICE) vehicle which access power by unidirectional. This one-way power delivery becomes a limitation for advanced EV with the regenerative braking feature, which the kinetic power of the vehicles is converted into electrical power. To test and measure this capability, a new chassis dynamometer is needed where the power delivery must be bidirectional. With that intention, this study proposes the usage of half-bridge bidirectional DC–DC converter (HBDC) as the Power Absorption and Delivery Unit (PADU) for a DC machine based dynamometer. PADU is controlled by modified Hysteresis Current Controller (HCC) and PID controller. The modified HCC and PID control power flow direction; back and forth during testing. The testing includes normal condition and regenerative braking condition. In normal condition, power is delivered by the DC machine whereas in regenerative braking condition, power is absorbed by the DC machine. Several test cases are considered; inclination test, declination test, normal drive condition, brake condition and stop condition. It is found that the HBDC successfully control the power flow in both normal condition and regenerative braking condition. As compared to conventional HBDC, modified HBDC reduces conduction loss with up to 28.21% reduction and switching loss with up to 7.69% reduction. To evaluate the power flow control, several power measurement points are taken in the simulation and comprehensive results are presented. Based on these results, the testing for an EV during normal condition and regenerative braking condition is achieved by successfully implement bidirectional power flow control in chassis dynamometer.